Nonlinear models for morphometric analysis in Bullfrog Tadpoles - Mansano, Cleber Fernando Menegasso; Pereira, Marcelo Maia; Peruzzi, Nelson José; Macente, Beatrice Ingrid; De StÉfani, Marta Verardino (UFBA - Universidade Federal da Bahia, 2016)
SUMMARY Biometric relationships are important to illustrate the growth of animals. When adjusted using nonlinear models, these relationships can provide important information that contributes to the improvement of breeding techniques. In this study, morphometric data as a function of weight obtained in four experiments involving bullfrog tadpoles were adjusted using Gompertz, Logistic, Von Bertalanffy and Brody nonlinear models and the best-fit model was determined. After fitting the parameters to the different models in each experiment, the models were compared based on confidence intervals (α = 0.05). The following criteria were used for selection of the best model: biological interpretation, residual mean square, coefficient of determination, graphic analysis, and number of iterations. Standard and total length data as a function of tadpole weight converged in the four models. The Logistic and Gompertz models had no biological interpretation for some datasets. The Brody model provided the lowest residual mean square and number of iterations for the variables studied in all experiments. The Brody relative growth rate (K) was lower for total length when compared to standard length, indicating a greater initial growth in standard length. The Brody model was the best to describe the growth in standard and total length of bullfrog tadpoles as a function of weight.

RESUMO As relações biométricas são importantes para ilustrar o processo de crescimento dos animais. Estas, quando ajustadas a modelos não-lineares, podem revelar informações importantes para a melhoria das técnicas de criação. O conjunto de dados morfométricos em função do peso, de quatro experimentos com girinos de rã-touro, foram ajustados aos modelos não-lineares de Gompertz, Logístico, Von Bertalanffy e Brody, com objetivo de verificar o melhor ajuste. Após a adequação dos parâmetros para os diferentes modelos em cada experimento seguiu-se com a comparação dos mesmos, por meio dos intervalos de confiança (α = 0,05). Os critérios para selecionar os modelos foram: interpretação biológica, quadrado médio do resíduo, coeficiente de determinação, análise gráfica e o número de iterações. Os dados de comprimentos padrão e total em função do peso dos girinos convergiram nos quatro modelos. Os modelos Logístico e Gompertz não apresentaram interpretação biológica para alguns conjuntos de dados. O quadrado médio do resíduo e número de iterações em todos os experimentos e variáveis estudadas apresentaram os menores valores para o modelo de Brody. Os valores de K dos modelos de Brody para comprimento total, quando comparados ao padrão, apresentaram-se menores, indicando que os animais apresentaram um crescimento inicial maior em comprimento padrão. O modelo de Brody foi o mais indicado para descrever o comprimento padrão e total em função do peso para girinos de rã-touro.
Análise morfométrica através de modelos não-lineares para girinos de rã-touro
Keywords: biometric relationship; frog farming; growth; length; comprimento; crescimento; ranicultura; relações biométricas